Evaluation of the risk factors for rhegmatogenous retinal detachment associated with choroidal detachment from the viewpoint of treatment patterns: a retrospective study - Kai Gao; Zi-Ye Chen; Zhuang-Ling Lin; Ya-Ping Liu; Bao-Yi Liu; Yuan Ma; Zi-Tong Chen; Rebiya●Tuxun; Lan Jiang; Zhuo-Jun Xu; Chin-Ling Tsai; Kun-Bei Lai; et al. (International Journal of Ophthalmology)
AIM: To compare the proportion of rhegmatogenous retinal detachment (RRD) associated with choroidal detachment (RRDCD) in the emergency surgery group with the routine inpatient surgery group and determine risk factors for RRDCD. METHODS: A total of 694 patients (694 eyes) diagnosed with RRD in the emergency surgery (the median duration of RRD was 5d) group were included from the Department of Ophthalmic Emergency, and 692 patients (eyes) in the routine inpatient surgery group (the median duration was 15d) were selected randomly from the Ocular Fundus Department. Demographics, refractive status, macular status, lens status, extent of retinal detachment, number of retinal breaks, duration of symptoms before surgery, and the incidence of RRDCD were compared. A logistic regression analysis was used to determine potential risk factors for RRDCD. RESULTS: Compared to the routine inpatient surgery group, the emergency surgery group had a significant less median time to surgery (P<0.001) and a decreased proportion of RRDCD (2.88% vs 10.84%, P<0.001). Logistic regression analysis revealed that a prolonged duration of RRD [OR 3.51, 95% confidence interval (CI) 1.98-6.23], pseudophakia/aphakia status [OR 2.74, 95%CI (1.50-4.98)], multiple retinal breaks [OR 1.67, 95%CI (1.03-2.70)], and a substantial extent of RRD [OR 11.58, 95%CI (7.12-18.84)] were independent risk factors for RRDCD. CONCLUSION: Emergency surgical pattern of RRD demonstrates a lower incidence of RRDCD. The adoption of an expedited surgical approach has the potential to reduce the duration of RRD, possibly correlating with a decreased risk of RRDCD development.